The Capital Structure of Regulated Firms - Yossef Spiegel; Daniel F. Spulber (Northwestern University, Kellogg School of Management, Center for Mathematical Studies in Economics and Management Science, 1991)
The equilibrium price, investment, and capital structure of a regulated firm are examined using a sequential model of regulation. The firm's capital structure is shown to have a significant effect on regulated prices, so that the firm's choice of debt and equity levels refelect regulatory responses. Moreover, debt financing weakens the incentive for regulators to "hold up" the firm so that leveraged firms can invest more than all-equity firms.
Keywords: L51; G32; G38; L9; 330; capital structure; regulation; investment; public utilities; bankruptcy